Analysis of caesarean sections using Robson 10-group classification system in a university hospital in eastern Ethiopia: a cross-sectional study. Issue 4 (4th April 2018) - Tura, Abera Kenay; Pijpers, Olga; de Man, Myrna; Cleveringa, Myrthe; Koopmans, Ingeborg; Gure, Tadesse; Stekelenburg, Jelle
Abstract : Objective: To analyse caesarean section (CS) using Robson 10-group classification system in an Ethiopian university hospital. Design: Cross-sectional study. Setting: A university hospital in eastern, Ethiopia. Participants: 980 women who underwent CS from January 2016 to April 2017. Main outcome: Robson groups (1–10—based on gestational age, fetal presentation, number of fetus, onset of labour and history of CS) and indications for CS. Results: Robson group 3 (multiparous women with single cephalic full-term pregnancy in spontaneous labour with no history of CS), group 5 (multiparous women with single cephalic full-term pregnancy with history of CS) and group 1 (single cephalic nulliparous women full-term pregnancy in spontaneous labour) were the major contributors to the overall CS at 21.4%, 21.1% and 19.3%, respectively. The three major indications for CS were fetal compromise (mainly fetal distress), obstructed labour (mainly cephalopelvic disproportion) and previous CS. Conclusion: Robson groups 3, 5 and 1 were the major contributors to the overall CS rate. Fetal compromise, obstructed labour and previous CS were the underlying indications for performing CS. Further study is required to assess the appropriateness of the indications and to reduce CS among the low-risk groups (groups 1 and 3).